Kontradiktif Pengaturan Hukum Yang Hidup Atas Formulasi Penjelasan Pasal 2 Ayat (1) Undang-Undang Nomor 1 Tahun 2023 Tentang Kitab Undang-Undang Hukum Pidana - Eko Ari Wibowo; Nafi’uddin Fauzi Mahfudh (JURNAL PENELITIAN SERAMBI HUKUM, 2026)
The law that lives in society is basically an original legal value of the Indonesian nation, so it is appropriate for the law that lives in society to have a place in the criminal law system in Indonesia. Policy formulation is basically part of the law enforcement system. With the presence of living legal formulations in society in the provisions of Law Number 1 of 2023 concerning the Criminal Code, law enforcement will have traditional values ??in future legal practices. However, with the presence of an explanation of the formulation of Article 2 Paragraph (1), it turns out that it has attracted the author's attention a little to discuss the essentials of a living law. In this research the author used a normative-juridical method, with descriptive analysis. The research results show that living legal provisions have been formulated systematically, starting from the Constitution of the Republic of Indonesia, Law Number 48 of 2009 concerning Judicial Power and Law Number 1 of 2023 concerning the Criminal Code. Then the contradiction in the existing legal regulations in the Elucidation of Article 2 Paragraph (1) lies in the sound of the formulation in the sentence that "Regional Regulations regulate customary criminal acts". The author suggests that in the future the existing law in regional regulations does not need to mention these customary offenses one by one, but it is sufficient to summon traditional community leaders during the trial to assess whether the actions committed by the defendant constitute a customary offense or not. However, the evidence and decision are still handed over to the judge through the criminal justice system.